Introduction - Xiaoyu Du (A+BE: Architecture and the Built Environment, 2019)
In our current age, sustainability is a key issue in the development of society, economy and environment. It is widely discussed that it is necessary to achieve a balance between the needs of people, business and nature. To maintain and possibly improve the built-up world in an ecological sense is a worldwide challenge for the current and next generation of architects, designers, technicians, public servants and decisionmakers on every level (Kristinsson, 2012). Health nature and human delight are important factors in creating new manmade living environment-city, neighbourhood and building-but these form no common basis for design. The building sector plays a significant role in the overall energy consumption, consuming over one-third of the global final energy consumption. Most of the energy is for the provision of lighting, heating, cooling and air conditioning. As human society develops, the energy demand of buildings could continuously increase globally. Therefore, reducing the energy consumption in the building sector is an important research topic. After decades of effort, to improve the efficiency of energy systems and to develop clean and new energy, architects, engineers and researchers have also tried to develop passive ways to reduce the energy consumption of buildings and to provide a comfortable living environment for occupants. More attention is paid to vernacular buildings in order to get inspiration for passive cooling and heating techniques.